'I'm not interested in research; i'm interested in services': How to better health and social services for transgender women living with and affected by HIV. (January 2022) - Everhart, Avery R.; Boska, Hayden; Sinai-Glazer, Hagit; Wilson-Yang, Jia Qing; Burke, Nora Butler; LeBlanc, Gabrielle; Persad, Yasmeen; Ortigoza, Evana; Scheim, Ayden I.; Marshall, Zack
Abstract: This paper presents results of a research priority setting process focused on trans women living with and affected by HIV across Canada. It features data from semi-structured interviews and focus groups conducted with a diverse group of 76 trans women in five urban centers across the country on how they have navigated health and social service programming within their geographic context. The results focus on the structure and types of services. Respondents offered simple, yet creative ways to address barriers to vital services based on their individual and collective experiences. Notably, participants stressed the need for 1) trans-friendly and trans-specific services, 2) integrated health services, and aid in navigating complex, overlapping systems, and 3) comprehensive community-based services. They also suggest employing trans women as care coordinators or case managers in order to foster more trans-friendly environments and empower community members. We identify concrete ways to improve health and social services at the level of service delivery and program design, as well as recommendations for future participatory research. We close with an interrogation of trans people, and trans women living with and affected by HIV in particular, as 'hard to reach' populations. Highlights: Research with trans women yields richer insights if trans-identified experts lead. Trans-friendly and trans-specific modes of service design and provision differ. Integrated services are vital, but must address nuance of transgender women's needs. Trans women are not hard to reach; rather, it is services that are hard to access. Our trans-led community-based participatory approach can and should be reproduced.